Effects of Dietary Acidifiers and Low Acid-Binding Capacity-4 (ABC-4) Formulation Strategies on Nursery Pig Performance and Fecal Dry Matter - Ethan B. Stas; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 725 pigs (DNA 241 × 600, initially 13.0 lb) were used to determine the effect of dietary acidifiers and other low acid-binding capacity at a pH of 4 (ABC-4) formulation strategies on nursery pig performance and fecal dry matter (DM). At weaning, pigs were randomly allotted to one of five dietary treatments. There were five pigs per pen and 29 replications per treatment across two facilities. Pigs were fed experimental diets in two phases with phase 1 provided with a feed budget of 5 lb/pig followed by phase 2 diets fed until d 24 post-weaning. The first three diets were formulated to approximately 200 and 250 meq/kg in phases 1 and 2, respectively, by using three different formulation strategies. The three formulation strategies included: 1) lowering the Ca:P ratio by 0.20, 2) addition of 0.6% formic acid (Amasil NA; BASF; Florham Park, NJ), and 3) replacing whey permeate (Dairylac 80; International Ingredients Corporation; St. Charles, MO) with crystalline lactose. Fumaric acid (Primary Products Ingredients Americas LLC, Decatur, IL) was included at 0.46% for all low ABC-4 diets across both phases. Diet 4 was a high ABC-4 diet formulated to be 100 meq/kg greater than the low ABC-4 diets. The first four dietary treatments contained 110 ppm of Zn provided by the trace mineral premix. Diet 5 was diet 4 with the addition of 3,000 and 2,000 ppm of Zn from ZnO in phases 1 and 2, respectively. Following phase 2, all pigs were fed a common corn-soybean meal-based diet until the completion of the study on d 38 post-weaning. In the experimental period (d 0 to 24) and overall (d 0 to 38), pigs fed the lactose replacement strategy had decreased (P < 0.05) ADFI compared to pigs fed the other low ABC-4 formulation strategies.In the experimental period (d 0 to 24) and overall (d 0 to 38), pigs fed the low ABC-4 diets had improved (P ≤ 0.022) F/G compared to pigs fed the high ABC-4 diet. In the experimental period (d 0 to 24), pigs fed the diet containing ZnO had increased (P ≤ 0.001) ADG and ADFI compared to pigs fed the high ABC-4 diet without ZnO. On all fecal collection periods (d 8, 17, and 24), pigs fed the low ABC-4 diets had increased (P ≤ 0.024) fecal DM compared to pigs fed the high ABC-4 diet. In summary, low ABC-4 diets improved feed efficiency and fecal dry matter regardless of the formulation strategy. However, replacing whey permeate with crystalline lactose decreased feed intake. In addition, pigs fed diets containing fumaric and formic acid had the same ending BW and ADG as those fed the high ABC-4 diet with ZnO.
Keywords: acid-binding capacity; acidifiers; calcium level; lactose source